To install click the Add extension button. That's it.

The source code for the WIKI 2 extension is being checked by specialists of the Mozilla Foundation, Google, and Apple. You could also do it yourself at any point in time.

4,5
Kelly Slayton
Congratulations on this excellent venture… what a great idea!
Alexander Grigorievskiy
I use WIKI 2 every day and almost forgot how the original Wikipedia looks like.
Live Statistics
English Articles
Improved in 24 Hours
Languages
Recent
Show all languages
What we do. Every page goes through several hundred of perfecting techniques; in live mode. Quite the same Wikipedia. Just better.
.
Leo
Newton
Brights
Milds

# Series multisection

In mathematics, a multisection of a power series is a new power series composed of equally spaced terms extracted unaltered from the original series. Formally, if one is given a power series

${\displaystyle \sum _{n=-\infty }^{\infty }a_{n}\cdot z^{n}}$

then its multisection is a power series of the form

${\displaystyle \sum _{m=-\infty }^{\infty }a_{qm+p}\cdot z^{qm+p}}$

where p, q are integers, with 0 ≤ p < q.

## Multisection of analytic functions

A multisection of the series of an analytic function

${\displaystyle f(z)=\sum _{n=0}^{\infty }a_{n}\cdot z^{n}}$

has a closed-form expression in terms of the function ${\displaystyle f(x)}$:

${\displaystyle \sum _{m=0}^{\infty }a_{qm+p}\cdot z^{qm+p}={\frac {1}{q}}\cdot \sum _{k=0}^{q-1}\omega ^{-kp}\cdot f(\omega ^{k}\cdot z),}$

where ${\displaystyle \omega =e^{\frac {2\pi i}{q}}}$ is a primitive q-th root of unity. This solution was first discovered by Thomas Simpson.[1] This expression is especially useful in that it can convert an infinite sum into a finite sum. It is used, for example, in a key step of a standard proof of Gauss's digamma theorem, which gives a closed-form solution to the digamma function evaluated at rational values p/q.

## Examples

### Bisection

In general, the bisections of a series are the even and odd parts of the series.

### Geometric series

Consider the geometric series

${\displaystyle \sum _{n=0}^{\infty }z^{n}={\frac {1}{1-z}}\quad {\text{ for }}|z|<1.}$

By setting ${\displaystyle z\rightarrow z^{q}}$ in the above series, its multisections are easily seen to be

${\displaystyle \sum _{m=0}^{\infty }z^{qm+p}={\frac {z^{p}}{1-z^{q}}}\quad {\text{ for }}|z|<1.}$

Remembering that the sum of the multisections must equal the original series, we recover the familiar identity

${\displaystyle \sum _{p=0}^{q-1}z^{p}={\frac {1-z^{q}}{1-z}}.}$

### Exponential function

The exponential function

${\displaystyle e^{z}=\sum _{n=0}^{\infty }{z^{n} \over n!}}$

by means of the above formula for analytic functions separates into

${\displaystyle \sum _{m=0}^{\infty }{z^{qm+p} \over (qm+p)!}={\frac {1}{q}}\cdot \sum _{k=0}^{q-1}\omega ^{-kp}e^{\omega ^{k}z}.}$

The bisections are trivially the hyperbolic functions:

${\displaystyle \sum _{m=0}^{\infty }{z^{2m} \over (2m)!}={\frac {1}{2}}\left(e^{z}+e^{-z}\right)=\cosh {z}}$
${\displaystyle \sum _{m=0}^{\infty }{z^{2m+1} \over (2m+1)!}={\frac {1}{2}}\left(e^{z}-e^{-z}\right)=\sinh {z}.}$

Higher order multisections are found by noting that all such series must be real-valued along the real line. By taking the real part and using standard trigonometric identities, the formulas may be written in explicitly real form as

${\displaystyle \sum _{m=0}^{\infty }{z^{qm+p} \over (qm+p)!}={\frac {1}{q}}\cdot \sum _{k=0}^{q-1}e^{z\cos(2\pi k/q)}\cos {\left(z\sin {\left({\frac {2\pi k}{q}}\right)}-{\frac {2\pi kp}{q}}\right)}.}$

These can be seen as solutions to the linear differential equation ${\displaystyle f^{(q)}(z)=f(z)}$ with boundary conditions ${\displaystyle f^{(k)}(0)=\delta _{k,p}}$, using Kronecker delta notation. In particular, the trisections are

${\displaystyle \sum _{m=0}^{\infty }{z^{3m} \over (3m)!}={\frac {1}{3}}\left(e^{z}+2e^{-z/2}\cos {\frac {{\sqrt {3}}z}{2}}\right)}$
${\displaystyle \sum _{m=0}^{\infty }{z^{3m+1} \over (3m+1)!}={\frac {1}{3}}\left(e^{z}-e^{-z/2}\left(\cos {\frac {{\sqrt {3}}z}{2}}-{\sqrt {3}}\sin {\frac {{\sqrt {3}}z}{2}}\right)\right)}$
${\displaystyle \sum _{m=0}^{\infty }{z^{3m+2} \over (3m+2)!}={\frac {1}{3}}\left(e^{z}-e^{-z/2}\left(\cos {\frac {{\sqrt {3}}z}{2}}+{\sqrt {3}}\sin {\frac {{\sqrt {3}}z}{2}}\right)\right),}$

${\displaystyle \sum _{m=0}^{\infty }{z^{4m} \over (4m)!}={\frac {1}{2}}\left(\cosh {z}+\cos {z}\right)}$
${\displaystyle \sum _{m=0}^{\infty }{z^{4m+1} \over (4m+1)!}={\frac {1}{2}}\left(\sinh {z}+\sin {z}\right)}$
${\displaystyle \sum _{m=0}^{\infty }{z^{4m+2} \over (4m+2)!}={\frac {1}{2}}\left(\cosh {z}-\cos {z}\right)}$
${\displaystyle \sum _{m=0}^{\infty }{z^{4m+3} \over (4m+3)!}={\frac {1}{2}}\left(\sinh {z}-\sin {z}\right).}$

### Binomial theorem

Multisection of a binomial expansion

${\displaystyle (1+x)^{n}={n \choose 0}x^{0}+{n \choose 1}x+{n \choose 2}x^{2}+\cdots }$

at x = 1 gives the following identity for the sum of binomial coefficients with step q:

${\displaystyle {n \choose p}+{n \choose p+q}+{n \choose p+2q}+\cdots ={\frac {1}{q}}\cdot \sum _{k=0}^{q-1}\left(2\cos {\frac {\pi k}{q}}\right)^{n}\cdot \cos {\frac {\pi (n-2p)k}{q}}.}$

## References

1. ^ Simpson, Thomas (1757). "CIII. The invention of a general method for determining the sum of every 2d, 3d, 4th, or 5th, &c. term of a series, taken in order; the sum of the whole series being known". Philosophical Transactions of the Royal Society of London. 51: 757–759. doi:10.1098/rstl.1757.0104.